Metabolite glues as a means of purine sensing and chemotherapeutic response - Samuel R. Witus; Megan M. Kober; Heegwang Roh; Zhi Yang; Fouad Choueiry; Avani S. Ghate; Denis V. Titov; Michael Rapé (Nature, 2026)
Abstract Molecular glues stabilize weak interactions to impart new functionalities to complexes 1–3 . Although molecular glues have been described in plant signalling and as human therapeutics 4,5 , it is unclear whether this modality provides endogenous regulation in human cells. Here we show that purine nucleotides are molecular glues that tether the rate-limiting enzyme in purine biosynthesis—phosphoribosyl pyrophosphate amidotransferase (PPAT)—to its inhibitor NUDT5. This mechanism allows cells to sense the levels of purines and to establish essential feedback control of their synthesis. We refer to such molecules as metabolite glues. Thiopurine chemotherapeutics 6 , which have been in clinical use since the 1950s, glue the same complex but adopt distinct orientations for enhanced function. Unlike most known glues, the PPAT–NUDT5 metabolite-glue pocket can adjust its conformation to notable compound alterations, enabling increased glue potency and improved on-target activity. We therefore identify endogenous metabolite glues as a mode of nutrient sensing that can be exploited for therapeutic benefit.